1981
DOI: 10.1103/physrevb.24.1691
|View full text |Cite
|
Sign up to set email alerts
|

Transport and optical properties ofTi1+xS2

Abstract: We report measurements of the dectrical resistivity, Hall coefficient, magnetoresistance, thermoelectric power, infrared reflectivity, and c-axis lattice parameter of single crystals of titanium disulfide Ti&+"S& with varying degrees of nonstoichiometry. The strong correlations we find between different measurements made on the same sample allow us to conclude that titanium disulfide is a semiconductor rather than a semimetal. Even though this fact is established, our most stoichiometric samples continue to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(39 citation statements)
references
References 23 publications
3
36
0
Order By: Relevance
“…Similarly, band calculations based on the augmented spherical wave (ASW) method by Fang et al, 9 the linear muffin-tin orbital (LMTO) method by Wu et al, [10][11][12] and the full-potential (FP)-LAPW method 13,14 showed that TiS 2 possessed a semimetallic ground state. Meanwhile, many experiments 15,16 have indicated that the electrical resistivity of TiS 2 almost exclusively exhibits metallic behavior, decreasing with decreasing temperature down to nearly 0 K. To date, no semiconductor behavior in the conductivity of TiS 2 has ever been observed experimentally. Hence, it is interesting and also significant (as mentioned below) to clarify the observed contradictory phenomena concerning the properties of TiS 2 .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Similarly, band calculations based on the augmented spherical wave (ASW) method by Fang et al, 9 the linear muffin-tin orbital (LMTO) method by Wu et al, [10][11][12] and the full-potential (FP)-LAPW method 13,14 showed that TiS 2 possessed a semimetallic ground state. Meanwhile, many experiments 15,16 have indicated that the electrical resistivity of TiS 2 almost exclusively exhibits metallic behavior, decreasing with decreasing temperature down to nearly 0 K. To date, no semiconductor behavior in the conductivity of TiS 2 has ever been observed experimentally. Hence, it is interesting and also significant (as mentioned below) to clarify the observed contradictory phenomena concerning the properties of TiS 2 .…”
Section: Introductionmentioning
confidence: 97%
“…To date, for instance, whether it is a semiconductor or semimetal has not been clarified. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Through measurements of the Hall coefficient, Seebeck coefficient, and resistivity as a function of pressure, Klipstein and Friend 2 found that the band overlap between S 3p states and Ti 3d states increased at a rate of 4.5 meV/kbar, and concluded that TiS 2 is a semiconductor with a gap of 0.18 ± 0.06 eV. The optical measurements of Greenway and Nische 3 indicated that TiS 2 is a semiconductor with a gap of 1 eV to 2 eV.…”
Section: Introductionmentioning
confidence: 99%
“…Transport properties of TiS 2 2 are strongly affected by its large off-stoichiometry. [11][12][13][14][15] were measured by the van der Pauw and Montgomery methods, respectively, using a lock-in technique in the temperature range from 4 to 300 K. Thermopower in this temperature range was measured by the conventional constant-∆T method. In-plane Hall resistivity up to 2 T was measured in the van der Pauw configuration by applying the magnetic field normal to the c-plane in the temperature range from 5 to 300 K. In-plane and out-of-plane thermal conductivities at room temperature were measured by the AC thermal diffusivity and the laser flush methods, respectively.…”
mentioning
confidence: 99%
“…The band gap of TiS 2 was investigated many times both experimentally [57][58][59][60][61][62][63][64][65] and theoretically [5,11,[66][67][68][69][70][71][72][73][74]. Experimental studies suggest that TiS 2 is a semiconductor with a small indirect band gap between 0.18 eV [63] and 0.56 eV [65].…”
Section: Band Structurementioning
confidence: 99%